Simulation of blood flow in abdominal aortic aneurysms treated with suprarenal and fenestrated stent grafts - Sun, Zhonghua; Chaichana, T.; Sangworasil, M. (RSNA, 2008)
The purpose of this study was to simulate the blood flow features in patients with abdominal aortic aneurysms treated with suprarenal and fenestrated stent grafts, which are two commonly used endovascular techniques to deal with complicated aneurysm necks.